Implementation of graduate employability skills SJT instrument in Universiti Utara Malaysia - Zakaria, Mohd Hafiz; Yatim, Bidin; Ismail, Suzilah (2014)
Assessing graduate employ ability skills before they enter the job market is very important because if they are lacking certain skills, improvement can be made through the process of training.In this study, a valid and reliable new instrument for measuring graduate employability skills using Situational Judgement Test (SJT) approach was implemented.The instrument consisted of 12 items representing five employ ability skills namely communication skill, professional ethics & morality, entrepreneurial skill, critical thinking in problem solving and personal quality.The purpose was to obtain a norm score for each of these skills.A survey was conducted using the SJT instrument on 1012 Universiti Utara Malaysia (UUM) local undergraduate final year students.The norm score was generated by employing BCA bootstrap technique. Scores guideline was created based on three levels (low, moderate and high).The outcomes indicated that the students possessed moderate level of communication skill, entrepreneurial skill, critical thinking in problem solving and personal quality but has high professional ethics & morality.